Health-Related Quality of Life in Children with HIV Infection—A Cross-Sectional Study from South India - Gopakumar, K. G.; Bhat, Kamalakshi G.; Joseph, Nitin; Shetty, Avinash K. (Journal of Pediatric Infectious Diseases, 2017)
Assessment of health-related quality of life (HRQoL) in children with HIV is crucial to improve the psychosocial well-being of this vulnerable population.The objective of this study was to assess the HRQoL of children with HIV infection aged between 5 and 18 years. The study was conducted in 144 children with HIV attending an antiretroviral therapy (ART) center in Karnataka to assess the HRQoL, using the PedsQL questionnaire. Total 144 children were included in the study, who had HRQoL with good physical (75.99 ± 13.46), psychosocial (71.01 ± 12.83), and total (72.43 ± 12.73) scores according to the child's perspective. Number of boys and children raised in foster homes were 51.3% (74) and 56% (81), respectively. Even though all children had complete adherence and had a good immunologic and clinical profile, we found that their HRQoL did not vary with stage of infection, duration of treatment, or immunologic status. Our findings underscore the importance of family-centered care for children living with HIV and advocate enhancing psychosocial and mental development to improve the HRQoL of children.
Keywords: quality of life; pediatric HIV; psychosocial; physical